The Effectiveness of Euclid's Algorithm Method in Solving Problems about FPB - Zakirman Zakirman; Wienda Gusta; Syelfia Dewimarni (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2022)
Many students are constrained in determining the FPB value of two numbers. The use of factor theorem methods has not been effective in helping students solve problems about FPB. Euclid's algorithm comes as a solution to make it easier for students to solve problems about FPB. This study aimed to test the effectiveness of Euclid's algorithm theorem in solving problems about FPB. This type of research is quasi-experimental and involves two classes: the experimental class (the application of Euclid's algorithm theorem) and the control class (using the factor tree method). The sample involved in the study was course V-A and V-B SDN 19 student Nan Sabaris. The instruments used in the study are questionnaires, observation sheets, and essay tests. Data collected in research activities is analyzed with an independent test of t-test samples. Before the data is analyzed, both data groups must first be normally distributed and homogeneous. The results of data analysis both in the form of questionnaire analysis, observation sheet, and analysis of test results showed a significant difference between the solution of FPB problems between experimental classes using Euclid theorems and control classes that use factor tree methods. Euclid's algorithm is a practical, easy-to-understand method, and the user does not take a long time in the process of the problem. The thing to note in applying Euclid's algorithm theorem is the understanding of the principle of division by students. Teachers need to pay attention to the extent of students' knowledge of the division material because this understanding affects students' performance in using Euclid's algorithm theorem to solve problems about FPB.